1938
DOI: 10.1210/endo-23-1-32
|View full text |Cite
|
Sign up to set email alerts
|

The Menopause a Consideration of the Symptoms, Etiology, and Treatment by Means of Estrogens

Abstract: NEW YORK CITYThe treatment of menopause symptoms by ovarian extracts dates back a full generation, but therapy by means of pure hormone preparations is of very much more recent origin. Large quantities of pure estrogens have become available only during the past 5 years. This report deals with the treatment of 200 cases of menopause by means of purified or crystalline estrogenic hormones (except one). These patients have been observed over a period of not less than 6 months and, on the average, not more than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Klaiber et al (1972);Servinghaus (1933), and Wiesbader and Kuszrok (1938) found that premenopausal depressed women with regular menstrual cycles had higher levels of plasma MAO activity, and oral estrogen therapy (Premarin 125 mg daily) normalized MAO activity and the depressed mood. These results suggest that estrogen deficiency may enhance metabolism of NE.…”
Section: Estrogensmentioning
confidence: 99%
“…Klaiber et al (1972);Servinghaus (1933), and Wiesbader and Kuszrok (1938) found that premenopausal depressed women with regular menstrual cycles had higher levels of plasma MAO activity, and oral estrogen therapy (Premarin 125 mg daily) normalized MAO activity and the depressed mood. These results suggest that estrogen deficiency may enhance metabolism of NE.…”
Section: Estrogensmentioning
confidence: 99%
“…The occurrence of depression in women not previously subject thereto, is fairly frequent at the menopause. In mild and moderately severe cases estrogen is almost a specific, improvement frequently ensuing in a matter of days (29, 30). We have also seen worthwhile results in mild and moderately severe involutional melancholia, but only rarely in the severe type.…”
Section: Serious Consequences Of a Drastic Decline In Body Estrogenmentioning
confidence: 99%